PRODUCTION OF GOLD FISH, CARASSIUS AURATUS (LINNAEUS) AND ITS ECONOMICS IN MEGHALAYA - MAHAPATRA, B. K.; VINOD, K.; MANDAL, S. (Journal of the Inland Fisheries Society of India, 2021)
The cold temperature prevailing in Meghalaya was found suitable for gold fish (Carassius auratus) breeding and culture. Breeding was recorded from 8 o C to 23 o C. A minimum of 500 eggs were recorded in 1+ year female where as 3000 eggs were laid by 3+ year female per spawning. Minimum time required for hatching was 65 hours at 23.5 o C and the maximum time was 98 hours at 8 o C. Average fertilization and hatching was 86% and 68% respectively. The number of spawn recorded per spawning per female varied from 334 to 1674. In the sequential rearing, the average growth of fish was 1.15 cm, 3.07 cm and 4.95 cm, respectively in 15, 30 and 45 days of rearing. The financial feasibility indicates viability of gold fish farming. Financial viability, indicators viz, Net Present Value (Rs. 637082), Benefit-Cost Ratio (3.11) and Internal Rate of Return (111 per cent) were estimated and found to be favourable for investment.Key words: Gold fish, breeding, culture, financial feasibility, northeast